KONSTRUKSI STRUKTUR TIGA DIMENSI FITOESTROGEN HASIL KONVERSI DARI SMILES STRING REPRESENTATIONS UNTUK SIMULASI PENAMBATAN MOLEKULER MENGGUNAKAN SOFTWARE PLANTS - Enade Perdana Istyastono; Nunung Yuniarti (Majalah Obat Tradisional, 2016)
Phytoestrogens have some important biological effects and could be employed as medicinal resources, for example as cancer chemopreventive agents. Phytoestrogen is defined as a phytochemical that has estrogenic or anti estrogenic effects. However, there is no database providing comprehensive list of phytoestrogen structures. In computer-aided drug discovery, the database is required to perform virtual screening for retrospective validation and structure-based drug design. The research presented in this article attempted to collect a comprehensive list of phytoestrogen structures. Subsequently, the structures were prepared in their three dimensional structures using SPORES1.3 for molecular docking simulations using PLANTS1.2. The ready-to-dock structures were then stored online as phytoestrogens.zip and could be downloaded from http://molmod.org/phytoestrogens.zip. This database contains 30 ready-to-dock unique phytoestrogens with total of 53 different configurations.